From Feminist Theory to Feminist Theology: Elizabeth Fiorenza’s Critical Approach to Women Liberation - Mary Winifreeda, S. (Jaffna Science Association, 2018)
Generally feminism is defined as the theory that promotes the social, economic, cultural and political emancipation of women. The feminist theology is the religious face of this theory of women liberation. It originates among the women who realize their situation and together work towards a change by breaking through the conventional forms of dominating theology and its arrangement with power. And it is not meant only for - women. It welcomes the cooperation of men, provided they are willing to give up their privileges. The goal is a fully integrated humanity of all. This research examiners Elisabeth Schüssler Fiorenza’s contributions to feminist theology. She is a radical Catholic feminist theologian. In this study, I focus on one of her book Transforming Visions: Explorations in Feminist The*logy. This book is divided into four sections that seek to reflect on the plight of the feminist struggles and their transforming visions. In this book she tries to take us from feminist theory to theology, through family struggles, and ultimately into a feminist vision of the Ecclesia of women, where God's love, justice and equality reign in the image of Divine Wisdom. I try to study how she explains feminist theology in a Euro- American social location and apply it our local situation whereby we also can open certain academic lines that can be of help in the emancipation of our own Tamil women in the given context.
Keywords: Feminism; Liberation; Theology; Feminist Theology